A STUDY OF ENGLISH TEACHERS’ VERBAL INTERACTIONAL FEEDBACK STRATEGY IN TEACHING ENGLISH AT SMAN 5 KOTA BENGKULU - Ami Pradana (Journal Of Dehasen Educational Review, 2021)
Teachers’ verbal interactional feedback is very important aspect in teaching and learning English in the classroom, because it aims to increase students’ motivation and let the students know their performance, and to motivate the students to talk more active. The objective of this study was to find out the strategy and its proportion used by English teachers’ in providing interactional feedback in teaching English at SMAN 5 kota Bengkulu. This research was a descriptive research that mixed quantitative and qualitative method. The subject of this research was three English teachers at SMAN 5 Kota Bengkulu who had been teaching in first year and second year. The data were collected by using observation checklist, and audio recorder. The results of this study show that the English teachers at SMAN 5 Kota Bengkulu applied all strategies in providing interactional feedback with different proportion. It was illustrated by some feedbacks that they frequently applied such as acknowledging an answer was the most dominant strategy used with 38.29%, then followed by praising with 19.32%, repeating students answer with 13.55%, expanding or modifying students’ answer with 11.55%, criticizing students answer with 8.96%, summarizing students answer with 7.17%, and indicating an incorrect answer with 5.58%. In brief, the teachers applied all strategies in giving verbal interactional feedback in teaching process with different proportion for each strategy